CONTAMINATION OF PUBLIC PARKS (JESÚS NAZARENO, AYACUCHO-PERU) WITH TOXOCARA EGGS - Málaga Cruz, Hernán (2017)
Th e current study established the presence of Toxocara spp. eggs in public parks of the Jesús de Nazareno district in the Ayacucho Region, Peru. Th is study evaluated the presence of Toxocara spp. eggs, degree of upkeep of public parks, presence of fences, and also, verifi ed whether a correlation exists between the presence of these eggs and the presence of dogs and children in the parks inspected. It was determined that 90% of public parks in the district of Jesús de Nazareno are contaminated with Toxocara eggs, a 70% have low contamination and a 20% have a moderate contamination. As for the presence of perimeter fences, the absence of these fences was observed in 60% of cases, the Eta analysis found a low association (0.15) between the presence of fences and the degree of contamination. Th e correlation between the presence of dogs with the presence of Toxocara eggs was low. Finally, the largest concentration of children is found in public playgrounds, where there degree of contamination is low, indicating that the infection risk decreases but potentially always could mean a public health problem.